Estudio Para La Implementación Del E-Commerce En La Empresa Óptica San Juan De La Ciudad De Neiva (2021)
This study is academic research aimed at identifying and implementing a significant improvement to a traditional (family) business, in charge of supplying the sale of products and services framed within a municipal ophthalmology company, its main source of income being the provision of the ocular medical evaluation service and the sale of lenses and frames for glasses. It is proposed to implement an improvement of the service, significantly favoring the coverage of the company, for which a business transition process was carried out from the physical or face-to-face commercial panorama to a virtual business model, thus being how the strategic services of the electronic commerce, seeking to have a greater reach (getting new customers and loyalty of old ones) and a higher level of financial income.